2009
DOI: 10.1371/journal.pone.0008058
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A/Albumin-Mineral Complexes Resembling Serum Calcium Granules and Putative Nanobacteria: Demonstration of a Dual Inhibition-Seeding Concept

Abstract: Serum-derived granulations and purported nanobacteria (NB) are pleomorphic apatite structures shown to resemble calcium granules widely distributed in nature. They appear to be assembled through a dual inhibitory-seeding mechanism involving proteinaceous factors, as determined by protease (trypsin and chymotrypsin) and heat inactivation studies. When inoculated into cell culture medium, the purified proteins fetuin-A and albumin fail to induce mineralization, but they will readily combine with exogenously adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
115
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(145 citation statements)
references
References 221 publications
(414 reference statements)
30
115
0
Order By: Relevance
“…In contrast, when occurring in the presence of lower calcium and phosphate concentrations at room temperature, CPP formation progresses only over weeks to months. 8,9,17 Under the established conditions, the 96-well format along with a measurement time of 10 hours allows the measurement of about 200 samples/d.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when occurring in the presence of lower calcium and phosphate concentrations at room temperature, CPP formation progresses only over weeks to months. 8,9,17 Under the established conditions, the 96-well format along with a measurement time of 10 hours allows the measurement of about 200 samples/d.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing number of illnesses supposedly associated with nanobacteria, some researchers believe pharmaceutical agents can help combat nanobacteria buildup (14,15). Biosensors are being developed that can distinguish biocolloids and nanobacteria biogenic particles on the basis of ring formation of polystyrene nanospheres in water drops (16).…”
mentioning
confidence: 99%
“…Other investigators -Martel and Young, 9 Wu et al, 6 and Raoult et al 10 -did not obtain the same result when they used the same method. Anti-CNP monoclonal antibodies have high sensitivity and low specificity, which explains the failure to achieve cross-reactions with serum protein (albumin and fetuin-A) in other studies.…”
Section: 2mentioning
confidence: 83%
“…Calcifying NP antigens and antibodies were detected significantly more often in CNP-containing diseases compared to controls. 2 Although many studies [5][6][7][8]10 proposed that CNPs might have the ability to form mineral-protein complexes in normal serum in physiological conditions, in reality, Kajander et al reported that this could not be totally true. 37 However, mineral-protein complexes have been shown in a gammairradiated serum study model by Martel and Young.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation